Atypical Manifestation of LPS-Responsive Beige-Like Anchor Deficiency Syndrome as an Autoimmune Endocrine Disorder without Enteropathy and Immunodeficiency - Bakhtiar, Shahrzad; Ruemmele, Frank; Charbit-Henrion, Fabienne; Lévy, Eva; Rieux-Laucat, Frédéric; Cerf-Bensussan, Nadine; Bader, Peter; Paetow, Ulrich (Frontiers in Pediatrics, 2016)
Monogenic primary immunodeficiency syndromes can affect one or more endocrine organs by autoimmunity during childhood. Clinical manifestations include type1 diabetes mellitus, hypothyroidism, adrenal insufficiency and vitiligo. LPS-responsive beige-like anchor protein (LRBA) deficiency was described in 2012 as a novel primary immunodeficiency, predominantly causing immune dysregulation and early onset enteropathy. We describe the heterogeneous clinical course of LRBA deficiency in two siblings, mimicking an autoimmune polyendocrine disorder in one of them in presence of the same underlying genetic mutation. The third child of consanguineous Egyptian parents (Patient 1) presented at six months of age with intractable enteropathy and failure to thrive. Later on he developed symptoms of adrenal insufficiency, autoimmune haemolytic anaemia, thrombocytopenia, and infectious complications due to immunosuppressive treatment. The severe enteropathy was non-responsive to the standard treatment and led to death at the age of 22 years. His younger sister (Patient 2) presented at the age of 12 to the endocrinology department with decompensated hypothyroidism, perioral vitiligo, delayed pubertal development, and growth failure without enteropathy and immunodeficiency. Using whole-exome sequencing (WES) we identified a homozygous frameshift mutation (c.6862delT, p.Y2288MfsX29) in the LRBA gene in both siblings. To our knowledge our patient (patient 2) is the first case of LRBA deficiency described with predominant endocrine phenotype without immunodeficiency and enteropathy. LRBA deficiency should be considered as underlying disease in pediatric patients presenting with autoimmune endocrine symptoms. The same genetic mutation can manifest with a broad phenotypic spectrum without genotype-phenotype correlation. The awareness for disease symptoms among non-immunologists might be a key to early diagnosis. Further functional studies in LRBA deficiency are necessary to provide detailed information on the origin of autoimmunity in order to develop reliable predictive biomarkers for affected patients.